The Caribbean Vice Admiralty Courts, 1763-1815; Indispensable Agents of an Imperial System - Craton, Michael (My University, 1968)
This thesis examines the nature and development of the British Vice Admiralty Courts in the West Indies, Bahamas and Bermuda between the end of the Seven Years' War and the end of the Napoleonic Wars, the heyday of "the First British Empire". After a general introduction and a chapter describing the origins of the Courts down to 1763, there are sections on personnel and procedures , appointments and patronage , the law applied by the Courts in their various functions, and relationships, metropolitan and colonial. A chronological treatment follows, of the American War of Independence, the interwar period 1783-93, and the period of greatest prosperity, sophistication and reform during the French Revolutionary and Napoleonic Wars, when the Courts were strongly influenced by Sir William Scott, the great Judge of the High Court of Admiralty. The thesis is rounded off by a short summary of conclusions.﻿
Keywords: History; History